Identitas dan Karakter Budaya Lokal pada Kemasan Makanan Oleh-Oleh - Nina Nurviana; Priyanto Sunarto; Achmad Syarief (Wimba : Jurnal Komunikasi Visual, 2012)
"Oleh-oleh"has become an important thing to buy. "Oleh-oleh" package with prominent characteristic of the local culture can be found in a small number of "oleh-oleh" shops or stalls. This characteristic might be hard to find in other areas. Nowadays, the number of such packaging is still limited. With its various cultures, Indonesia should have become a great source of inspiration to develop packaging design"oleh-oleh". This background triggered the idea that "oleh-oleh" packaging design has great potential to be developed. Such "oleh-oleh" packaging can be considered to have a unique position for several reasons. In addition to its design, its existence in the area of tourism activities and cultural environment has been continually living side by side with the identity where it is marketed. "Oleh-oleh" packaging will be deeply assessed by using a combination method of qualitative and quantitative approaches. Qualitative approach is used to identify the physical and graphic of it. The theory underlining this study is a packaging design theory and theories related to the form of culture. To identify the character of the packaging, theory associated with uniqueness, exotics and emotions are employed. Making use of questionnaire, consumer perceptions of the design are collated. To identify the average opinion of the respondents, a quantitative approach with Semantic Differential assessment method is adopted. The study of the food "oleh-oleh" packaging which can be useful source in design planning, shows that: (1) form, materials and how to package are the aspects influencing the construction of the package; (2) cultural context viewed at the packaging is cultural context seen as exotics, nostalgic experience, visual experience, (3) recognition from consumers is needed to show evidence of physical experience to the place visited and the desire to collect (4) aspects of culture on the packaging can be considered as an opportunity to increase sales; (5) the efforts of food manufacturers in decorating the package is considered quite successful in highlighting the uniqueness and the attractiveness of the appearance.